Evaluation of the Efficacy of Low-Particle-Size Toothpastes against Extrinsic Pigmentations: A Randomized Controlled Clinical Trial - Andrea Butera; Maurizio Pascadopoli; Simone Gallo; Alessia Pardo; Giulia Stablum; Marco Lelli; Anna Pandolfi; Andrea Scribante (MDPI AG, 2023)
Stain-removing domiciliary protocols are focused on the elimination of dental extrinsic pigmentations by the application of abrasive toothpastes, extensively available in commerce. The goal of the present study is to evaluate the efficacy of two different stain removal molecule-formulated toothpastes by the reduction of clinical parameters: the micro-cleaning crystals and activated charcoal. A total of 40 participants with extrinsic dental pigmentations were enrolled and divided into two groups: a Control group, assigned to a toothpaste with micro-cleaning crystals (Colgate Sensation White); and a Trial group, with microparticle-activated charcoal toothpaste (Coswell Blanx Black). At T0 (baseline), T1 (10 days), T2 (1 month), and T3 (3 months), clinical parameters, including Lobene stain index calculated for intensity and extension, plaque control record, and bleeding on probing, were measured. Statistically significant differences were found in both groups (p < 0.05): a reduction of extrinsic pigmentation, both in intensity and extension, was obtained in the Control group, but their total elimination could be achieved only in the Trial group with the activated charcoal molecule, though without significant difference between the groups (p > 0.05). No intergroup differences were found for each timeframe for PCR, BoP, LSI-I, and LSI-E. Both tested toothpastes can be recommended for domiciliary oral hygiene of patients with extrinsic pigmentations.